2017
DOI: 10.1016/j.oceaneng.2017.09.061
|View full text |Cite
|
Sign up to set email alerts
|

The hydrodynamic forces on a circular cylinder in proximity to a wall with intermittent contact in steady current

Abstract: We present a three-dimensional Large Eddy Simulations (LES) study on the hydrodynamics of a circular cylinder close to a wall. Intermittent gaps between the cylinder and wall, forming spanning and non-spanning sections along the span are considered. This geometry setting represents an idealized model of pipelines laid on an uneven seabed. As compared to that of the corresponding spanwise-uniform cylinders, the drag coefficient on spanning sections is generally smaller, while the drag on non-spanning sections i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The effect of acceleration on hydrodynamic forces was calculated at all bodies. The hydrodynamics forces of a circular cylinder close to a wall were considered by Tong et al [28]. They used the large eddy simulations (LES) method for the simulation of flow over a 3-D circular cylinder near a wall.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of acceleration on hydrodynamic forces was calculated at all bodies. The hydrodynamics forces of a circular cylinder close to a wall were considered by Tong et al [28]. They used the large eddy simulations (LES) method for the simulation of flow over a 3-D circular cylinder near a wall.…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been carried out with regards to protecting submarine pipelines from devastating extreme surge and wave damage during their service periods. Tong et al [2] presented a three-dimensional Large Eddy Simulation (LES) study on the hydrodynamics of a submarine pipeline located close to a wall impacted by current. Results showed that the drag coefficient on spanning sections of the pipeline is generally smaller than that of non-spanning sections, and due to the pressure gradient around the submarine pipeline, vortices shedding can be generated.…”
Section: Introductionmentioning
confidence: 99%